EGFR/MAPK Signaling Regulates the Proliferation of Drosophila Renal and Nephric Stem Cells. - Li, Z.; Liu, S.; Cai, Y. (Journal of Genetics and Genomics [Yi chuan xue bao], 2015)
Tissue homeostasis, accomplished through the self-renewal and differentiation of resident stem cells, is critical for the maintenance of adult tissues throughout an animal's lifetime. Adult Drosophila Malpighian tubules (MTs or fly kidney) are maintained by renal and nephric stem cells (RNSCs) via self-renewing divisions, however, it is unclear how RNSC proliferation and differentiation are regulated. Here we show that EGFR/MAPK signaling is dispensable for RNSC maintenance, but required for RNSC proliferation in vivo. Inactivation of the EGFR/MAPK pathway blocks or greatly retards RNSC cell cycle progression; conversely, over-activation of EGFR/MAPK signaling results in RNSC over-proliferation and disrupts the normal differentiation of renablasts (RBs), the immediate daughters of RNSC divisions. Our data further suggest that EGFR/MAPK signaling functions independently of JAK/STAT signaling and that dMyc and CycE partially mediate EGFR/MAPK signaling in MTs. Together, our data suggest a principal role of EGFR/MAPK signaling in regulating RNSC proliferation, which may provide important clues for understanding mammalian kidney repair and regeneration following injury.